Answer:
r = 3
General Formulas and Concepts:
Pre-Algebra
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
Equality Properties
Explanation:
Step 1: Define
4r - 6 = 6
Step 2: Solve for r
- Add 6 to both sides: 4r = 12
- Divide 4 on both sides: r = 3
Step 3: Check
Plug in r into the original equation to verify it's a solution.
- Substitute in r: 4(3) - 6 = 6
- Multiply: 12 - 6 = 6
- Subtract: 6 = 6
Here we see that 6 does indeed equal 6.
∴ r = 3 is the solution to the equation.